PENENTUAN OPTIMASI PARAMETER PERMESINAN TERHADAP KEKASARAN BAJA ST 42 HASIL PROSES BUBUT MENGGUNAKAN METODE TAGUCHI - Alfiansyah Riady; Mastiadi Tamjidillah (Mechanical Engineering Department, Faculty of Engineering, Universitas Lambung Mangkurat, 2017)
This study aims to increase the Productivity of Rolling Using Taguchi Method. In the old industrial company the work of a product greatly affects the work cost and the level of machinary productivity, so it needs a method in order to optimize the level of productivity. The Taguchi method can be used to optimize to get the best machining productivity level. This research uses ST 42 steel material with conventional lathe machining process. It is known in this study to obtain the best roughness or optimum parameters used in the spindle rotation is 490 rpm, feeding motion 0.11 mm/rev, 0.2 mm feeding depth. the most influential factor in this research is spindle rotation 41.6%, feeding 46.3% while the eating depth is less influential that is equal to 5.4%.